Liquidity, innovation, and endogenous growth - Malamud, Semyon; Zucchi, Francesca (Journal of Financial Economics, 2019)
We build a model of endogenous, innovation-driven growth in which innovative firms have costly access to outside financing and hoard cash reserves to maintain financial flexibility. We show that financing frictions slow down Schumpeterian creative destruction by discouraging entry. As a result, financing frictions importantly affect the composition of growth, by reducing the contribution of entrants but spurring the contribution of incumbents. We investigate the net impact of these countervailing effects on the equilibrium growth rate and welfare.